Greenhouse Gas Response to Simulated Precipitation Extremes in Alpine River Source Wetlands During the Growing Season - Ziwei Yang; Kelong Chen; Yuqiang Tian; Ying Li; Hairui Zhao; Ni Zhang (Atmosphere)
Against the backdrop of climate warming leading to an increase in extreme weather events, extreme precipitation events have become more frequent, and the impact of changes in precipitation on ecosystems cannot be ignored. There is a scarcity of field in situ observational data on greenhouse gas emissions during the growing season for alpine wetlands, especially for alpine river source wetlands, which limits our understanding of the ability of alpine wetland ecosystems to convert between carbon sources and carbon sinks and also hinders our comprehension of the primary effects of extreme precipitation events on wetland ecosystems. In this study, we investigated the main greenhouse gas emission fluxes in two consecutive growing seasons (May to September) under the conditions of natural control (CK), 75% increase in precipitation (IP), and 75% decrease in precipitation (DP) through in situ field simulations of extreme precipitation in an alpine source wetland in the Qinghai Lake Basin of the Qinghai–Tibet Plateau. The results indicate the following: (1) The extreme precipitation increase (IP) treatment did not significantly increase CO2 fluxes; it promoted CH4 flux emissions by 168.2% and N2O flux emissions by 178.4% over the two growing seasons. The extreme precipitation decrease treatment had a non-significant impact on CO2 fluxes; it inhibited CH4 emission fluxes by 96.8% and promoted N2O emission fluxes by 137.8%. (2) During the growing season, CO2 fluxes were 2.2% lower in the IP treatment than in the DP treatment under the two precipitation patterns; the CH4 flux under the IP treatment is 84.1% higher than that under the DP treatment, and N2O fluxes were 43.8% lower in the IP treatment than in the DP treatment. CH4 fluxes were the most sensitive to precipitation changes. (3) The extreme changes in precipitation were not the main influencing factor for CO2 fluxes, while CH4 fluxes were primarily affected by precipitation changes. (4) During the entire growing season, IP reduced the global warming potential (GWP) by 9.03%, and DP decreased GWP by 8.40%. These results suggest that the primary driver of CO2 fluxes in alpine river source wetlands remains temperature factors; in scenarios where extreme climate events occur frequently, both extreme increases and decreases in precipitation have inhibitory effects on the global warming potential of alpine river source wetlands.